PERANCANGAN PROTOTYPE PLTSA DENGAN TURBIN IMPULS SATU TINGKAT - Angga Tata Pradana, I Putu; Indra Partha, Cok Gede; Janardana, I Gusti Ngurah (Program Studi Teknik Elektro UNUD, 2023)
Garbage is a very serious problem in the coastal areas of the beaches in Bali, the management of waste sent from the sea is not maximized. One alternative way of managing waste is using a waste power plant (PLTSa) that can generate electricity. The purpose of this study was to determine the effect of current, torque and power on the PLTSa prototype by designing a single stage impulse turbine, the method used in this study was descriptive quantitative. Tests on the PLTSa prototype used a single-stage impulse turbine with a runner diameter of 44 cm and a total of 75 turbine blades. This prototype uses a nozzle with a nozzle diameter of 6mm and a boiler from a 13.6 Kg freon gas cylinder with a boiler output steam of 3 bar and a water capacity of 9 liters to get the highest average turbine rotation of 1470 rpm and the highest generator rotation of 2460, so that at single stage impulse turbine gets the highest voltage of 16.44 Volts, the highest current of 2.28 Amperes and the highest output power of 23.32 Watt with a torque of 0.18 Nm so this prototype has an efficiency of 11.1%.